P.176 Perioperative factors predict two year trajectories of pain and disability following anterior cervical discectomy and fusion. (June 2022) - El-Mughayyar, D; Adams, T; Bigney, E; Cunningham, E; Richardson, E; Attabib, N; Abraham, E; Manson, N; Small, C; Leroux, A; Kolyvas, G; ,; et al.
Abstract : Background: A subset of patients experience poor outcomes following anterior cervical discectomy and fusion (ACDF). Our study aimed to identify postoperative trajectories of disability, neck/arm pain and determine baseline measures that predict subgroup membership. Methods: Patients with cervical spondylotic radiculopathy undergoing ACDF are presented. Prognostic factors comprised demographic, health and surgery-related variables. Study outcomes were trajectories of neck disability index scores, numeric rating scales for neck/arm pain modeled with latent-class growth analysis. Associations were explored using robust Poisson models and reported with risk ratios and 95% confidence intervals. Results: Patients (N = 352; mean (SD) age = 50.9(9.5) years, 43.8% female) identified trajectories for disability (excellent=45.3%, fair=39.2%, poor=15.5%), arm pain (excellent=24.5%, good=52.0%, poor=23.5%), and neck pain (excellent=13.7%, good=63.1%, poor=23.2%). Greater physical and mental health-related quality of life were associated with a reduced risk of poor outcome(per SD, 0.40[0.30, 0.53]-0.80[0.65, 0.99]), while higher risk for depression (per SD, 1.36[1.12, 1.65]-2.26[1.84, 2.78]), longer wait time(per 90 days, 1.31[1.05, 1.63]-1.64[1.20, 2.24]), and longer procedure time (per 30 min, 1.07[1.03, 1.10]-1.08[1.05, 1.12]) were associated with an increased risk of poor outcome for all outcomes. Poor disability was increased with self-reported depression(3.03[1.76, 5.21]), greater neck-to-arm pain ratio (2.63 [1.28 to 5.40]), ASA score > 2(2.26[1.33, 3.83]), and preoperative opiates (2.05[1.18, 3.56]), while preoperative physiotherapy (0.51[0.30, 0.88]), spinal injections (0.48[0.23 to 0.98]), and regular exercise (0.44 [0.24, 0.79]) decreased risk. Receiving compensation and smoking were associated with poor outcome for neck pain. Remaining candidate prognostic factors were not associated with clinical outcome. Conclusions: Perioperative factors were shown to decrease risk of poor outcomes for pain and disability two years following ACDF.